ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB (STUDI KASUS : SMP NEGERI 5 KOTA JAMBI) - Malagandi, Sesuci Yogbi; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2017)
In processing the school academic data of Junior High School 5 Jambi City, it was found that the school still usesconventional method. As a result, there are some problems appeared during the processing of students data, teachersdata, students’ scoring data, and the most common problems are loosing the data in the main school data report. Thepurpose of this research is to analyze the needs of based web information system at Junior High School 5 Jambi byusing UML (Unified Modeling Language). The result of this research is an academic information system that canhelp teachers and staffs process students data, teachers data, and make the scoring system easier and integrated eachother. The information system performed through this research is in the form of teaching materials, teachers andstudents data, score data, and information for new school candidate, and information for the alumni of Junior HighSchool 5. It’s expected that the result of this research can be implemented in schools to revise the weaknesses of theprevious system. The recommendation for this research is that the design of this system needs to be improved so thatit can be used effectively at Junior High School 5 Jambi and the further research can be completed with data safetysystem. Hopefully, this research can give a great contribution toward the improvement of information and technologysystem.